INVESTIGATION OF RELATIONSHIP BETWEEN CONTROL PROBABILITY INDICATORS AND PERFORMANCE CHARACTERISTICS OF NAVIGATION PARAMETERS - Сущенко, О. А. (Proceedings of National Aviation University (archive), 2021)
A method is proposed to establish the relationship between the indicators of the probability of control and the performance of the meters of navigation parameters. The analysis of the methodical component of control probability is performed.